Kitab Sunan An-Nasā’ī (Biografi, Sistematika, dan Penilaian Ulama) - Nurkholijah Siregar (Hikmah, 2018)
The first two of the books "al-Kutūb al-Sittah are known by the names" two books of al-ṣaḥīḥ or ṣaḥīḥayn ", ie Shahih Bukhari and Sahih Muslim with different dignity of validity. Meanwhile, the last four "al-kutub al-sittahs" are known as Sunan Abī Dāūd, Sunan al-Turmużi, Sunan al-Nasā'i and Sunan ibnu Mājah. Imam an-Nasā'ī composes two books, namely al-Sunan Kubrā (the main sunan and summarized as as-Sunan as-ṣughrā (the secondary sunan) .The present book is as-sunan sugra, also called Sunan an-Nasā'ī belongs to one of the "al-Kutūb al-Sittah", the book of hadith shahih al-Mujtabā min as-Sunan.The number of hadith contained in it is 5.761 hadith.In this book there are hadith shahih, hasan, and also dhaif, which is accompanied by explanations of its level.